2013
DOI: 10.1136/bjsports-2013-092459.9
|View full text |Cite
|
Sign up to set email alerts
|

Tendons: Time to Revisit Inflammation?

Abstract: It is currently widely accepted that chronic tendinopathy is caused by a degenerative process devoid of inflammation. Current treatment strategies have focused on physical treatments including eccentric exercises, peritendinous injections of blood or blood products and interruption of painful stimuli. Results have been at best moderately good and at worst a failure.The evidence for degeneration alone as the cause of tendinopathy is surprisingly weak. There is compelling evidence that inflammation is a key comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 43 publications
1
33
0
1
Order By: Relevance
“…Schubert et al revealed demonstrated presence of macrophages and lymphocytes (using immunohistochemical techniques), in a chronic Achilles tendon pathology (duration of symptoms was 6-120 months) and granulocytes in a short time after acute rupture of the Achilles tendons [18]. Other authors demonstrated indirect signs of inflammatory response found in chronic tendons disorders -mediators of inflammation: IL-1, IL-6, TGF-β, substance P [19]. A smaller body of literature exists on chronic LHBT pathologies.…”
Section: Clusters Of Capillariesmentioning
confidence: 96%
See 1 more Smart Citation
“…Schubert et al revealed demonstrated presence of macrophages and lymphocytes (using immunohistochemical techniques), in a chronic Achilles tendon pathology (duration of symptoms was 6-120 months) and granulocytes in a short time after acute rupture of the Achilles tendons [18]. Other authors demonstrated indirect signs of inflammatory response found in chronic tendons disorders -mediators of inflammation: IL-1, IL-6, TGF-β, substance P [19]. A smaller body of literature exists on chronic LHBT pathologies.…”
Section: Clusters Of Capillariesmentioning
confidence: 96%
“…This is illustrated by a review of literature focused on 32 studies evaluating effectiveness of NSAID in tendinopathy, whereas 9 of 32 were prospective and placebo controlled and only 5 of them revealed reduction of painful conditions [22]. Different study investigated effectiveness of corticosteroids injections -only short-term clinical improvement was reported [19]. Authors point at the side-effects of corticosteroids injections: skin atrophy, decreased tendon strength and integrity, infections, possibility of spontaneous tendon rupture.…”
Section: Clusters Of Capillariesmentioning
confidence: 99%
“…Indeed, we found 96 DEGs to be annotated to "proteolysis" of which 67 were up-390 regulated in the HiO 2 HiT+ ( Figure 4C). Among them we found various extracellular proteases such as 391 matrix metalloproteinases (MMP 8,9,10,13,27), intracellular proteases involved in lysosomal 392 degradation such as cathepsins (cathepsin A, B, C, D, F, O, S, Z), and proteasome-related proteins 393 (PSMA 8, PSMB 3,8,9,).…”
mentioning
confidence: 99%
“…Tendinopathy severity is graded by its histopathological score, characterized by the extent of 36 disorganized collagen matrix, abnormal cell shape, presence of inflammation, increased cellularity, 37 vascularization and neuronal ingrowth [24][25][26][27][28]. These hallmarks of disease intimately involve tissue 38 turnover and proteolytic breakdown of the ECM [29][30][31][32].…”
mentioning
confidence: 99%
“…Sharma & Maffulli, 2005) It is a cause of anterior knee pain and is primarily a clinical diagnosis, although Doppler ultrasound can have additional benefit in diagnosis (Peers & Lysens, 2005). The literature regarding the cause of tendinopathies is continually evolving and there is currently debated over whether it is a noninflammatory or inflammatory process (Khan et al, 2002;Rees et al, 2013). Differential diagnoses include patellofemoral pain syndrome, fat-pad syndromes, meniscal tears, and cartilage degeneration (Warden & Brukner, 2003).…”
mentioning
confidence: 99%